2022
DOI: 10.1021/acs.chemrestox.1c00402
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Titanium Dioxide Nanoparticles on Mammalian Cell Cycle In Vitro: A Systematic Review and Meta-Analysis

Abstract: Although most studies that explore the cytotoxicity of titanium dioxide nanoparticles (nano-TiO2) have focused on cell viability and oxidative stress, the cell cycle, a basic process of cell life, can also be affected. However, the results on the effects of nano-TiO2 on mammalian cell cycle are still inconsistent. A systematic review and meta-analysis were therefore performed in this research based on the effects of nano-TiO2 on the mammalian cell cycle in vitro to explore whether nano-TiO2 can induce cell cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 118 publications
0
12
0
Order By: Relevance
“…Besides, this type of surface modification can reduce the potential toxicity of unmodified TiO 2 NPs, which is reported in recent publications. 5 In the following, some recent publications will be presented in which the TiO 2 NPs have been modified with such types of organic modifiers to prepare the efficient therapeutic TiO 2 NPs.…”
Section: Biological Applications Of Modified Tio2npsmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides, this type of surface modification can reduce the potential toxicity of unmodified TiO 2 NPs, which is reported in recent publications. 5 In the following, some recent publications will be presented in which the TiO 2 NPs have been modified with such types of organic modifiers to prepare the efficient therapeutic TiO 2 NPs.…”
Section: Biological Applications Of Modified Tio2npsmentioning
confidence: 99%
“…Besides, this type of surface modification can reduce the potential toxicity of unmodified TiO 2 NPs, which is reported in recent publications. 5 In the following, some recent publications will be presented in which the TiO 2 NPs have been modified with such types of organic modifiers to prepare the efficient therapeutic TiO 2 NPs. The surface modification of TiO 2 NPs with organic dyes, especially porphyrins, has attracted growing interest as it can broaden the absorption range of TiO 2 NPs from the UV region to the visible region.…”
Section: Photo- Thermo- and Sonodynamic Effects Of Modified Tio 2 Nps...mentioning
confidence: 99%
See 2 more Smart Citations
“…8,10,[12][13][14] At higher concentrations, TiO 2 nanoparticles cause reproductive toxicity in both females and males, [15][16][17] and induce oxidative stress that leads to cell damage, inflammation, and adverse immune responses. 9,11,12,17 Systematic review and metaanalysis have demonstrated that TiO 2 nanoparticles disrupt the mammalian cell cycle in vitro, 18 and disturb glucose and lipid homeostasis in mice and rats. 11,12 The nanomaterial has also been found to impact the digestive tract, increasing chronic intestinal inflammation and disorders of the intestinal barrier, and disrupting the normal functions of the gastrointestinal tract.…”
Section: In Vitro and In Vivo Effects Of Tio 2 Nanoparticlesmentioning
confidence: 99%